DIFFERENCES OF TUMOR MASSES AND HEMOGLOBIN LEVELS IN CERVICAL CANCER SQUAMOUS CELL TYPE PATIENTS TREATED WITH COMBINATION OF PACLITAXEL AND CARBOPLATIN CHEMOTHERAPY - Noviyani, R.; Suwiyoga, K.; Lesmana, I.; Niruri, R.; Tunas, K.; Budiana,; I N. K. (BALI MEDICAL JOURNAL, 2014)
Background: Paclitaxel and carboplatin are standard operating procedure for chemotherapy treatment of cervical cancer squamous cell carcinoma at Sanglah General Hospital, Bali-Indonesia. Chemotherapy improves outcome of cancer treatment. However, chemotherapy brings also a variety of adverse effects and complications. This study aims to evaluate the therapeutic and adverse effects of chemotherapy in patients with squamous cell cervical cancer. Methods: This is a case study of six patients with cervical cancer underwent chemotherapy paclitaxel and carboplatin 3-series at Sanglah General Hospital, Bali-Indonesia during January to November 2013. The therapeutic effect of chemotherapy was assessed from cervical cancer tumor mass measured before and after chemotherapy 3-series. The adverse effect of chemotherapy was determined from hemoglobin levels measured before and after chemotherapy. Data were analyzed using a paired t-test with a level of confidence of 95% using the SPSS to find out the differences. Results: In this study we found that there is a difference between tumor mass pre and post 3 series chemotherapy within p < 0.05. In term of toxic effect, we also obtained that there were difference of hemoglobin between pre and post of treatment within p < 0.05. Conclusion: Paclitaxel carboplatin as a chemotherapy drug in patients with cervical cancer is highly recomended when seen from the effects of reduced tumor size, and has a low side effect of anemia (anemia grade 1).